COVID-19 infection history as a risk factor for early pregnancy loss: results from the electronic health record-based Southeast Texas COVID and Pregnancy Cohort Study - Micaela N. Sandoval; Michelle R. Klawans; MacKinsey A. Bach; Jennifer Mikhail; Edward A. Graviss; Tru Cao; Jacqueline G. Parchem; Junaid Husain; Eric Boerwinkle (BMC Medicine)
Abstract Background The effects of SARS-CoV-2 infection before or during pregnancy on pregnancy outcomes are still largely unknown. We hypothesized that COVID-19 in early pregnancy is a risk factor for adverse pregnancy outcomes, particularly miscarriage. Methods We examined the relationship between COVID-19 and adverse pregnancy outcomes, including spontaneous abortion, ectopic pregnancy, and preterm delivery in a large, retrospective, electronic health record (EHR)-based cohort, from 2019 to 2023. Generalized estimating equation modeling was performed to identify risk factors for adverse pregnancy outcomes. Study exposures included COVID-19 before pregnancy, COVID-19 during pregnancy, age, race/ethnicity, comorbidity burden, and neighborhood-level social vulnerability. Results In the Southeast Texas Pregnancy and COVID Cohort (26,783 pregnancy episodes), the risk of miscarriage among pregnancy episodes with a miscarriage, livebirth, or delivery outcome was 6.3% (1514/ 24,119). In multivariable modeling, history of both mild and moderate to severe COVID-19 before pregnancy were associated with miscarriage (adjusted odds ratio (aOR) 2.48, confidence interval (CI) 2.21–2.78 and aOR 2.81, CI 1.8–4.38, respectively). Additionally, in the same model, both mild and moderate to severe COVID-19 in the first trimester were associated with miscarriage (aOR 2.31, CI 1.96–2.72 and aOR 2.45, CI 1.12–5.35, respectively). Conclusions COVID-19 both prior to and during pregnancy was identified as a risk factor for spontaneous abortion in this study sample. These findings highlight the importance of COVID-19 vaccination and post-COVID management for pregnant people and those planning a pregnancy.